PENGARUH HARGA EMAS DUNIA,HARGA MINYAK DUNIA DAN NILAI TUKAR USD TERHADAP HARGA SAHAM LQ45 - Pranita, Fera Lufhidarani; Riko Sutriyadi (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to analyze the influence of global gold prices, global oil prices, and the USD exchange rate on LQ45 stock prices on the Indonesia Stock Exchange. Global gold and oil prices are considered global indicators that influence investor sentiment, while the USD exchange rate reflects external forces affecting domestic economic stability. The data used is monthly time series data from 2021-2023, analyzed using multiple linear regression. The results show that global gold prices, global oil prices, and the USD exchange rate influence LQ45 stock prices. This finding indicates that investors in the Indonesian capital market pay attention to global macroeconomic conditions. This research is expected to serve as a reference for investors and policymakers in understanding the dynamics of the Indonesian capital market.